Aerodynamical design of a low velocities wind tunnel - Quispe Gonzáles, C. A. (2014)
This paper aims to develop the aerodynamical design and the geometric detrmination of a low veñocities wind tunnel. Was elected an Eiffel type open wind tunnel, according to the required conditions in the test chamber, such as the area and maximum air velocity in the test section; we propose the constructive layout with the tunnel elements and the geometry of them. We performe calculations to determine the flow veloctiy, the cross section and the aerodynamical losses in the characteristic sections of the instalation. We determine the required fan power and it’s selection according to the local market conditions.